Public Awareness of Outlying Michigan Agricultural Experiment Stations - Eileen Lehnert; Dick Divelbiss (Journal of Applied Communications, 1982)
The location of specialized agricultural research sites in areas of production removed from the parent land-grant university's campus has undoubtedly contributed to the present strength and stature of American agriculture.